2018
DOI: 10.32441/jaset.v1i3.181
|View full text |Cite
|
Sign up to set email alerts
|

Improve the bonding material properties used to strengthen concrete beams

Abstract: The subject of the research deals with the study of the effect of recycling and addition of some cheap and locally available materials on the properties of the adhesive material (Epoxy) used to strengthen concrete beams. Where the study included the addition of glass powder, brick powder and porcelain powder to the adhesive material and with different ratios of the weight of the adhesive material     (0, 0.25, 0.5, 0.75, 1 and 1.25). After conducting laboratory tests proved the results of the study that the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This is may be due to a relatively low tensile strength of jute fibers as compared to the carbon fibers. Most previous research and studies indicate that the tensile strength of the untreated jute fibers does not exceed 200 MPa, while for the carbon fibers it may reach 5 times its value in reinforcement steel [22]. Figure 8 indicated that increasing the width of jute fiber to 15 cm leads to increase the load carrying capacity of beams by 11.12% as compared with the reference beams.…”
Section: Groups Of Beamsmentioning
confidence: 84%
See 2 more Smart Citations
“…This is may be due to a relatively low tensile strength of jute fibers as compared to the carbon fibers. Most previous research and studies indicate that the tensile strength of the untreated jute fibers does not exceed 200 MPa, while for the carbon fibers it may reach 5 times its value in reinforcement steel [22]. Figure 8 indicated that increasing the width of jute fiber to 15 cm leads to increase the load carrying capacity of beams by 11.12% as compared with the reference beams.…”
Section: Groups Of Beamsmentioning
confidence: 84%
“…A type of artificial fibers widely used, consisted of 99% dark carbon with a density of 1790 kg/m 3 and tensile strength of 3900 MPa, available on the local markets in the form of roll with 45.7 m length and 305-610 mm width. It is usually used in reinforcing concrete and steel structure to increase shear and flexural strength [22].…”
Section:  Carbon Fibersmentioning
confidence: 99%
See 1 more Smart Citation